Aspek Imunologis pada Pemphigus Vulgaris - Saraventi Saraventi; Elza Ibrahim Auerkari (Faculty of Dentistry, Universitas Indonesia, 2015)
Pemphigus vulgaris is a relatively uncommon autoimmune disease marked with blister appearance of the skin tissue and mucosal membrane, resulting in loss of intercellular adhesion as well as the intact of epithelial cells, or so-called acantholysis. In this autoimmune disease the immune system forms autoantibodies attacking desmoglein, a specific protein at the skin tissue. The predisposing factors are presumed to include genetic and ethnic origin of the patient. Although at first usually without symptoms, after proceeding to the ulcerating stage the disease can result in fatal complications. Considering that almost 60% of the cases are first manifested in the oral mucosa, it is important that the dentists are aware of the basic etiology and immunology of the disease for correct diagnosis and therapy. This work reviews the etiopathogenesis of Pemphigus vulgaris, with emphasis on immunological aspects and immunotherapy.